2015
DOI: 10.1371/journal.pone.0139956
|View full text |Cite
|
Sign up to set email alerts
|

Cadmium-Induced Hydrogen Accumulation Is Involved in Cadmium Tolerance in Brassica campestris by Reestablishment of Reduced Glutathione Homeostasis

Abstract: Hydrogen gas (H2) was recently proposed as a therapeutic antioxidant and signaling molecule in clinical trials. However, the underlying physiological roles of H2 in plants remain unclear. In the present study, hydrogen-rich water (HRW) was used to characterize the physiological roles of H2 in enhancing the tolerance of Brassica campestris against cadmium (Cd). The results showed that both 50 μM CdCl2 and 50%-saturated HRW induced an increase of endogenous H2 in Brassica campestris seedlings, and HRW alleviated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 65 publications
1
16
0
Order By: Relevance
“…Researchers have found that some abiotic stresses increase endogenous H 2 production in higher plants, and H 2 could alleviate damage induced by abiotic stresses [12,13]. Wu et al reported that H 2 alleviated Cd stress through ROS detoxification by reestablishing glutathione homeostasis [22]. Chen found that HRW pretreatment remarkably attenuated heat stress-induced lipid peroxidation and antioxidant dysregulation in cucumber leaves [23].…”
Section: H 2 -Evolving and H 2 -Uptake Activities Existed In Pm Vesicmentioning
confidence: 99%
“…Researchers have found that some abiotic stresses increase endogenous H 2 production in higher plants, and H 2 could alleviate damage induced by abiotic stresses [12,13]. Wu et al reported that H 2 alleviated Cd stress through ROS detoxification by reestablishing glutathione homeostasis [22]. Chen found that HRW pretreatment remarkably attenuated heat stress-induced lipid peroxidation and antioxidant dysregulation in cucumber leaves [23].…”
Section: H 2 -Evolving and H 2 -Uptake Activities Existed In Pm Vesicmentioning
confidence: 99%
“…Research has demonstrated that the content of GSH reduction is important in maintaining a redox environment [71]. H 2 might be an important regulatory factor in improving the tolerance of Brassica campestris seedlings against Cd, primarily by governing GSH homeostasis [72]. Dai et al [73] suggested that HRW alleviated Cd toxicity chiefly by reducing oxidative damage promoting sulfur compound metabolism and maintaining nutrient element homeostasis in alfalfa.…”
Section: Heavy Metal Stressmentioning
confidence: 99%
“…Enhancing the activities of the antioxidant enzyme [8] Cole Cd stress affected the balance of glutathione Governing reduced glutathione homeostasis [72] Alfalfa Cd stress obviously inhibited alfalfa seedling growth…”
Section: Plant Species Abiotic Stress and Its Effect H 2 Roles Under mentioning
confidence: 99%
“…In plants, H 2 was found to play roles in root formation by interacting with the nitric oxide and haem oxygenase-1/carbon monoxide pathways [8,9]. Interestingly, accumulating reports have shown that H 2 production is elevated in many plant species under abiotic stresses, such as paraquat, NaCl, high light, UV-A, UV-B, and heavy metal stresses, and H 2 can further act as a regulator in plants coping with abiotic stresses [5,[10][11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, sulfur and GSH metabolism are important processes in plants coping with Cd [23][24][25][26]. Recent reports have indicated that H 2 could enhance Cd tolerance by increasing antioxidant capacities, including the gene expression of superoxide dismutase (SOD), peroxidase (POD), ascorbate peroxidase (APX), and catalase (CAT), and by reestablishing reduced glutathione homeostasis in Medicago sativa and Brassica campestris, respectively [15,27]. However, the underlying mechanism governing glutathione metabolism in H 2 -induced Cd tolerance has not been fully elucidated.…”
Section: Introductionmentioning
confidence: 99%